2023
DOI: 10.33215/sbr.v3i1.885
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Sustainability of Non-Governmental Organizations in the developing world

Abstract: NGOs provide support services in developing countries when governments are unable to improve the growth indicators. There exists a requirement for sustainable NGOs that can help fill the gap between the needs of the people and the scarce resources available in developing countries. This study aimed to identify essential factors that are internally controllable by the NGO and to reflect on the impact of the internally controllable factors on the NGO’s sustainability. The study used established theories to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 105 publications
0
3
0
Order By: Relevance
“…The developmental opportunities of SMEs and the use of human resource skills are connected with SMEs to form an approximate enterprise percentage of 99% with 99.7% in developing countries (Al Busaidi et al, 2019). The SMEs businesses provide for the direct contribution of employment, where SMEs critical success factors are contributing to 60% of the global workforce (Gumel & Bardai, 2023). The Gross domestic product (GDP) contribution of the world economy through SMEs is 90% to theUnited Kingdom (UK), 95% to the United States of America (USA), and 97% in Japan.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The developmental opportunities of SMEs and the use of human resource skills are connected with SMEs to form an approximate enterprise percentage of 99% with 99.7% in developing countries (Al Busaidi et al, 2019). The SMEs businesses provide for the direct contribution of employment, where SMEs critical success factors are contributing to 60% of the global workforce (Gumel & Bardai, 2023). The Gross domestic product (GDP) contribution of the world economy through SMEs is 90% to theUnited Kingdom (UK), 95% to the United States of America (USA), and 97% in Japan.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Tanzania, an assessment conducted to inform sustainability established that only 16.6% of NGOs perceived themselves as financially sustainable, 58.8% felt that their financial sustainability was seasonal, and a quarter (24.6%) confirmed that they were sustainable (Ministry of Community Development, 2022). NGOs strive for better resource management, transparency, and stakeholder communication (Gul & Swapnil, 2023). Notably, Enterprise Resource Planning (ERP) systems have gained attention as potential tools that bolster sustainability through their touted benefits of transparency, accountability, and efficiency (BARNA, 2022;Dedan, 2019;Nzuki, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Financial growth of the NGOs in the Lake Region Economic Block has been fluctuating since 2010, exacerbated by a declining trend from 2019 to 2022, creating a need for investigation. The financial sustainability and growth of an organization as measures of the organization's ability to meet its financial and programmatic obligations, according to NGOs Co-ordination Board (2020), Gul & Morande (2023), Makeche & Chowa (2023) Varghese, Joe, & Ajukuria (2021) investigated on financial sustainability of non-profit organization in North East India and established relationship between donor and income diversification significantly correlate with sustainability. Others require progressive integration to strike funding stability and growth sustainability alongside the foundational and effective attainment of their goals.…”
Section: Introductionmentioning
confidence: 99%